COMPARISON OF UV-VIS SPECTROPHOTOMETRIC AND HPLC METHODS IN THE ANALYSIS OF RETINOIC ACID AND HYDROQUINONE CONTENT IN FACE CREAMS: A LITERATURE REVIEW - Syifni, Moza Aulia; Utami, Marsah Rahmawati (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
UV-Vis spectrophotometry and HPLC are commonly used for the analysis of hydroquinone and retinoic acid, as both instruments offer a combination of accuracy, sensitivity, and ease in detecting and quantifying these compounds. UV-Vis is quick and simple to detect the content of materials based on light absorption, while HPLC is superior in separating and analyzing compounds in complex mixtures with high precision. The purpose of this literature review is to compare UV-Vis Spectrophotometry and HPLC methods for analyzing hydroquinone and retinoic acid, and a comparison was performed by examining method validation data between UV-Vis spectrophotometry and HPLC. The method applied involves a review of various related research journals, utilizing the Publish or Perish application using the Google Scholar and Semantic Scholar search engines. The results and conclusions of this study recommend HPLC as the method of choice for the identification of harmful substances, such as retinoic acid and hydroquinone, in face creams. Keywords: retinoic acid, hydroquinone, face cream, uv-vis spectrophotometry, HPLC